Laboratory Examinations in the Diagnosis of Dengue Hemorrhagic Fever: A Systematic Literature Review - Putu Ristyaning Ayu Sangging; Muhammad Purwono Prasetyo; Muhammad Nasrullah Nur Shiddiq; Intan Rahma Aprilia; Khalila Alya Mukhbita; Siti Aqila Zahra (Jurnal Kesehatan Metro Sai Wawai, 2025)
Dengue Hemorrhagic Fever (DHF) is an infectious disease caused by the dengue virus and remains a major public health problem in Indonesia. Early and accurate diagnosis is crucial for determining appropriate management and preventing fatal complications. This systematic literature review aimed to evaluate and synthesize evidence on laboratory diagnostic methods for DHF across Southeast Asia. A comprehensive search was conducted across Pubmed, ScienceDirect, Scopus, Google Scholar and DOAJ for studies published between 2015 and 2025, using keywords such as “Dengue Hemorrhagic Fever,” “Laboratory Diagnosis,” and “Southeast Asia.” Inclusion criteria encompassed peer-reviewed studies reporting empirical on hematological, serological, or molecular laboratory test for DHF, while reviews without empirical finding studies unrelated to dengue diagnosis were excluded. Found on database 40 after screening, 22 studies met the inclusion criteria and were analyzed. NS1 antigen testing plays a crucial role in the early phase of infection, while IgM and IgG serological tests are useful in identifying the immunological phase of the disease. Meanwhile, RT-PCR is a highly sensitive method for directly detecting the presence of the virus. Combining several testing methods has been shown to improve diagnostic accuracy, both in terms of sensitivity and specificity. However, optimal implementation of these tests still faces challenges such as limited resources, cost, time, and differences in laboratory capabilities at various levels of health facilities. Therefore, strengthening laboratory capacity, standardizing testing methods, and implementing a combination testing strategy are needed to improve the reliability of dengue diagnosis. This approach is expected to support early detection, accelerate treatment, and strengthen efforts to control dengue outbreaks nationally.